Aquaporins as salivary protein biomarkers for xerostomia and the effects of xerostomia on oral health related quality of life in patients with periodontitis attending combined Military Hospital, Lahore - Atif, Saira (2022)
Xerostomia is a debilitating condition of oral dryness which may lead to numerous oral health conditions affecting oral health-related quality of life (OHRQOL). The general objectives of this study were to identify the potential of using salivary aquaporin (AQP)-3, AQP-4, and AQP-5 proteins as biomarkers for xerostomia in patients with periodontitis and to investigate the effects of xerostomia on OHRQOL. In this descriptive study, 140 healthy participants, 20 – 55 years old, with Community Periodontal Index (CPI) score ≥ 2 were included through systematic random sampling. Shortened Xerostomia Inventory (SXI) was used for subjective assessment of xerostomia, while unstimulated saliva was collected for its objective measurement. Patient with SXI score ˃ 5 was considered xerostomic; score 6 – 8 as grade 1, and score 9 – 15 as grade 2 xerostomia. Shortened Oral Health Impact Profile (S-OHIP) questionnaire was utilised to assess OHRQOL. Quantification of AQP-3, AQP-4, and AQP-5 was done by enzyme-linked immunosorbent assay (ELISA). After removing extreme outliers, data of 132 participants were analysed. Probability value was set at 5%. Non-parametric tests were used for data analyses. Xerostomia was reported in 78% of the patients with periodontitis. Grade 1 xerostomia was reported in 74.8% whereas, grade 2 xerostomia in 25.2% of the periodontitis patients with xerostomia. OHRQOL was significantly poor in xerostomics compared to non xerostomics, p = .001, and in grade 2 compared to grade 1 xerostomia, p = .001. Unstimulated salivary flow rate was significantly lower in periodontitis patients with grade 1 compared to grade 2 xerostomia, p = .013. Concentration of AQP-3 was significantly higher in xerostomics compared to non-xerostomics, p < .001. Moreover, concentration of AQP-5 was significantly reduced in grade 2 compared to grade 1 xerostomia, p = .002. In the patients with periodontitis, there were significant correlations between SXI and S-OHIP (p < .001), SXI and AQP-3 (p = .004), AQP-3 and AQP-4 (p = .001), unstimulated salivary flow rate and AQP-4 (p = .035), and unstimulated salivary flow rate and AQP-5 (p = .007). SXI was a suitable predictor for poor OHRQOL. Moreover, S-OHIP score and AQP-3; and S-OHIP score and AQP-5 were suitable predictors of xerostomia and grade 2 xerostomia, respectively. In conclusion, salivary AQPs are suitable protein biomarkers for xerostomia in patients with periodontitis. It is important to manage xerostomia before it affects oral health by early detection using these biomarkers, as xerostomia is considerably prevalent and causes a deterioration of OHRQOL.